PENGARUH PENGUASAAN KOSAKATA TERHADAP KEMAMPUAN BERBICARA - Permadi, Rudi (Program Studi Pendidikan Agama Islam, 2024)
The students' ability to speak English in the Islamic Religious Education Study Program at the Tasikmalaya Islamic Institute is relatively low. One factor that influences this is the lack of vocabulary mastered. The worst effect of their lack of speaking skills is that they cannot express their brilliant mindset. This research aims to determine the effect of vocabulary mastery on speaking ability. The sample involved was 50 students of the Islamic Religious Education Study Program for the 2023/2024 Academic Year Semester 1. The sampling technique used a random sampling technique. Researchers used a quantitative survey. The research results show that there is a positive influence of vocabulary mastery on students' speaking ability because the significance value of speaking ability is 0.003 or smaller than 0.005.